The survey of Seira Lubbock, 1870 (Collembola, Entomobryidae, Seirinae) from Iberian Peninsula and Canary Islands, including three new species - Cipola, Nikolas Gioia; Arbea, Javier; Baquero, Enrique; Jordana, Rafael; Morais, José Wellington De; Bellini, Bruno Cavalcante (Zootaxa, 2018)
Here we present a survey of Seira fauna from Iberian Peninsula and Canary Islands, including the description of three new species from Spain: Seira barrai sp. nov., Seira betica sp. nov. and Seira burgersi sp. nov., the latter with unprece-dented antennal morphology for Seira. Five species from Western Europe are redescribed and their dorsal detailed chaetotaxy is revealed for the first time: S. domestica (Nicolet), S. dinizi Gama, S. ferrarii Parona, S. mantis Zeppelini & Bellini and S. pini Jordana & Arbea, the first two from type locality, and the latter two based on analysis of the type material. A note on chaetal interpretation of the first abdominal segment for Seira is presented. An identification key to 31 species with known dorsal chaetotaxy from Western Palearctic region is also provided, including a discussion on dense macrochaetotaxy present in Palearctic and Oriental species and its reduction in species from others biogeographic regions.